(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
At first glance, it is paradoxical that more people suffer from gastrointestinal bleeding, against the background of an emerging trend towards a decrease in the incidence of peptic ulcers, especially gastric ulcers. This trend is largely due to the widespread use of nonsteroidal anti-inflammatory drugs (NSAIDs ) , which cause erosions and ulcers of the digestive tract.